Student Perceptions of Performance-Based Assessments for In-Person and Online Courses - Chu, Man-Wai; Craig, Heather; Hoey, Felecia (Alberta Journal of Educational Research, 2024)
COVID-19 social distancing measures forced many university courses to be offered online. The performance-based assessments originally designed for in-person learning may not work well in online environments. This study investigated students’ perceptions of performance-based assessments, and their associated resources, during a course that was offered both in-person and online. The results from 312 undergraduate education students (n = 248 in-person and n = 64 online) indicated all the resources for one of the two assessments were rated statistically significantly higher by students who attended the course in-person. This indicated students who completed the course in-person had a stronger interaction with the assessment resources and rating having higher cognitive and affective skills needed to perform a similar assessment task in their future classrooms. Online students indicated some resources, such as assessment instructions and scoring rubrics, should be better explained during the course for more clarity regarding expectations.